Migration test and safety assessment of polyurethane adhesives used for food-contact laminated films. (March 2020) - Yan, J.W.; Hu, C.; Tong, L.H.; Lei, Z.X.; Lin, Qin-Bao
Highlights: Identify and detect potential migrants in adhesive laminates by GC–MS. Safety assessment of potential migrants was conducted by the threshold of toxicological concern. Six potential migrants are detected, three of which migrate to food simulant isooctane, while others don't. Cross section has insignificantly effect on the migration behavior. Graphene fails to have a substantial impact on migration behavior due to the agglomeration. Abstract: Migration test and safety assessment of polyurethane adhesives commonly used for food-contact laminated films are experimentally studied. Six harmful migrants from isocyanate residues and additives in adhesives are identified by combined GC–MS with NIST index and retention time of standard products. A series of migration tests regarding "LDPE-adhesive-LDPE" sandwiching laminated films are carried out, aiming to unfold the effects of temperature-time conditions, cross section and nanomaterials on the migration of identified compounds into food simulant isooctane. The results reveal that three of the six identified compounds, i.e., KH-560, 2, 4-DTBP and DMPA, may migrate into isooctane. Temperature is found to be the most important factor on the migration behavior. From the slight effect of cross section area on migration of compounds, it can be concluded that compounds easily diffuse into substrates and migrate into isooctane by penetrating through the substrates rather than cross section. We also found that adding graphene and functionalized graphene neither promote the migration nor inhibit. For safety assessment, threshold of toxicological concern method is alternatively used to evaluate the migration. The estimated daily intakes of KH-560 and DMPA in solvent-free polyurethane adhesive laminated films exceed the safety threshold recommended by threshold of toxicological concern, while those in solvent-based adhesive laminated films do not.